Implementation of da'wah for Bugis community in Sabah: A review - Saifulazry Mokhtar; Kasoma Thia; Irma Wani Othman; Mohd Khairi Lebai Ahmad; Mohd Azri Ibrahim (International Journal Of Modern Education (IJMOE), 2025)
Distributing Islamic pamphlets is a demand and trust that has been entrusted to every Muslim. A Muslim who carries out da'wah means that they have continued the call of the Prophet PBUH to spread Islam in the eyes of the world. Even so, there are still preachers who fail in their preaching calls because they do not understand the ins and outs of the struggle for the Prophet PBUH. This study aims to see the implementation of da'wah that is suitable for the Bugis community in Sabah who still adhere to the customs and rituals of their ancestors before. This study uses qualitative methods and participates in the landscape of life of the Bugis community. The findings of this study found several methods of da'wah implementation that are suitable to be applied to the Bugis community in Sabah such as using the approach of al-hikmah, mujadalah, taaruf, da'wah bi al-hal, the attraction of preachers, da'wah bi al-lisan and preachers as counsellors. The appropriate da'wah approach used according to the wishes of the da'wah recipients is undoubtedly the main indicator and determinant of success in Islamic da'wah activities.